2011
DOI: 10.1007/s10641-011-9948-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement and conservation of inland fisheries resources in China

Abstract: The inland aquatic ecosystem in China have been largely influenced by large-scale economic activities and over-exploitation of aquatic resources. Fisheries resource enhancement and conservation activities have been carried out throughout China. These activities include establishing artificial fish habitat and hatchery, releasing juvenile fish to rivers and lakes, forbidding illegal fishing, and setting up natural reserves. The purpose of these activities is to restore the quantity of inland fisheries resources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…The inland aquatic ecosystem in China has been largely influenced by large‐scale economic activities (Chen et al . ). Hydrological alterations are the largest external threat to fish biodiversity in these freshwater lakes (Fu et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…The inland aquatic ecosystem in China has been largely influenced by large‐scale economic activities (Chen et al . ). Hydrological alterations are the largest external threat to fish biodiversity in these freshwater lakes (Fu et al .…”
Section: Discussionmentioning
confidence: 97%
“…Sethi et al (2010) reported that MTL could be sensitive not only to fishery-induced changes at the ecosystem level but also to economic and technological factors. The inland aquatic ecosystem in China has been largely influenced by large-scale economic activities (Chen et al 2012). Hydrological alterations are the largest external threat to fish biodiversity in these freshwater lakes (Fu et al 2003;Ru & Liu 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Bighead carp ( Hypophthalmichthys nobilis ) and silver carp ( H. molitrix ) are the major exploited food fish species and are native to water systems in China. However, reduced natural resources of these fishes has been a severe problem because of habitat fragmentation or shrinkage resulting from dam construction, water pollution, and the long‐term overfishing in major waters of China (Chen, Li, & Wang, 2012; Hu, Hua, Zhou, Wu, & Wu, 2015). In recent years, the genetic diversity of populations of Yangtze River has been studied intensively (Pang, Yu, & Tong, 2015; Yu, Pang, Yu, Tong, & Shen, 2016; Zhang et al, 2013), which has provided large amounts of molecular evidence to aid our understanding of certain populations (or species).…”
Section: Introductionmentioning
confidence: 99%